Human development and capabilities. - Boni, Alejandra (Taylor and Francis, 2013)
Globally, universities are the subject of public debate and disagreement about their private benefits or public good, and the key policy vehicle for driving human capital development for competitive knowledge economies. Yet what is increasingly lost in the disagreements about who should pay for university education is a more expansive imaginary which risks being lost in reductionist contemporary education policy. This is compounded by the influences on practices of students as consumers, of a university education as a private benefit and not a public good, of human capital outcomes over oth.